Cytochrome bd in Mycobacterium tuberculosis: A respiratory chain protein involved in the defense against antibacterials. (May 2020) - Mascolo, Ludovica; Bald, Dirk
Abstract: The branched respiratory chain of Mycobacterium tuberculosis has attracted attention as a highly promising target for next-generation antibacterials. This system includes two terminal oxidases of which the exclusively bacterial cytochrome bd represents the less energy-efficient one. Albeit dispensable for growth under standard laboratory conditions, cytochrome bd is important during environmental stress. In this review, we discuss the role of cytochrome bd during infection of the mammalian host and in the defense against antibacterials. Deeper insight into the biochemistry of mycobacterial cytochrome bd is needed to understand the physiological role of this bacteria-specific defense factor. Conversely, cytochrome bd may be utilized to gain information on mycobacterial physiology in vitro and during host infection. Knowledge-based manipulation of cytochrome bd function may assist in designing the next-generation tuberculosis combination chemotherapy.